2016
DOI: 10.3324/haematol.2016.151779
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant cyclophosphamide versus anti-thymocyte globulin as graft- versus -host disease prophylaxis in haploidentical transplant

Abstract: Severe graft-versus-host disease is a major barrier for non-T-celldepleted haploidentical stem cell transplantation. There is no consensus on the optimal graft-versus-host disease prophylaxis. This study compared the two most commonly used graft-versus-host disease prophylaxis regimens (post-transplant cyclophosphamide-based vs. the anti-thymocyte globulin-based) in adults with acute myeloid leukemia reported to the European Society for Blood and Bone Marrow Transplantation. A total of 308 patients were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 35 publications
6
86
1
Order By: Relevance
“…However, we have not found such an effect in our study. In addition, Ruggeri et al reported that a Post‐Cy‐without ATG‐based regimen can achieve a lower incidence of GVHD than an ATG‐without Post‐Cy regimen in adult patients with AML, suggesting that any effect on GVHD rates seen in our study is linked to Post‐Cy administration regardless of ATG usage.…”
Section: Discussionsupporting
confidence: 92%
“…However, we have not found such an effect in our study. In addition, Ruggeri et al reported that a Post‐Cy‐without ATG‐based regimen can achieve a lower incidence of GVHD than an ATG‐without Post‐Cy regimen in adult patients with AML, suggesting that any effect on GVHD rates seen in our study is linked to Post‐Cy administration regardless of ATG usage.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that the population included in this study partially overlaps with the recently published data by Ruggeri et al, 27 in which haplo-HSCT using PTCy was compared with ATG platforms, showing significantly better LFS, lower incidence of GVHD, and nonrelapse mortality of the former regimen compared with the latter in patients with AML in complete remission. In the study by Ruggeri et al, 27 the incidence of aGVHD was not influenced by the stem cell source or intensity of conditioning regimens in multivariate analysis adjusting for the adopted GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 47%
“…In the study by Ruggeri et al, 27 the incidence of aGVHD was not influenced by the stem cell source or intensity of conditioning regimens in multivariate analysis adjusting for the adopted GVHD prophylaxis. We hypothesize that the inclusion of advanced status diseases and ALL patients in our cohort could partly explain these results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial approaches aimed at expanding UCB with various cytokine cocktails met with little successes [12,13]. Fortunately, novel strategies aimed at increasing the number of hematopoietic stem and progenitor cells (HSPCs) transplanted for UCBT or at increasing their ability to home to their bone marrow niches have been much more encouraging and might lead in the future to a regrowth of adult UCBT in Europe, a transplant approach currently challenged by the development of T-cell repleted HLA-haploidentical stem cell transplantation [42][43][44]. These strategies have consisted of double UCBT with or without expansion of one of the 2 UCB units, cotransplanting a single UCB unit with HLA-haploidentical CD34+ cells (haplo-cord transplantation), or increasing UCB HSC homing to marrow niches via direct intrabone UCB administration, pulse treatment with dmPGE2 or enforced fucosylation [13,45] (Table 2).…”
Section: Novel Approaches To Hasten Hematologic Recovery After Ucbtmentioning
confidence: 99%